HUBUNGAN KINERJA GURU DI MASA PERALIHAN KURIKULUM MERDEKA BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPA KELAS V SD NEGERI 040443 KABANJAHE TAHUN AJARAN 2022/2023 - Juwita Tindaon; Veronika Br Sembiring (Universitas Quality, 2023)
The problem in this study was that the students' Internship learning outcomes were less than optimal. The samples in this study were fifth grade students, totaling 30 students. The purpose of this study was to find out whether there was a relationship between teacher performance during the transitional period of the independent learning curriculum towards student learning outcomes in class V science subject, Public Elementary School 040443 Kabanjahe, Academic Year 2022/2023. This type of research is product moment correlation. Data analysis used uses the Product Moment Correlation formula. Based on the analysis of the data, it was obtained an overview of the work performance of the teachers of the State Elementary School 040443 Kabanjahe for the 2021/2022 Academic Year, the average value was 59.60, which was included in the poor category. An overview of the results of learning science for class V students at Public Elementary School 040443 Kabanjahe for the 2021/2022 Academic Year obtained an average value of 75.93, including the quite capable category. There is a significant relationship between teacher work performance and science learning outcomes for fifth grade students at Public Elementary School 040443 Kabanjahe for the 2021/2022 academic year, because the t value in calculation = 4.942 > t in table = 2.05.